Unemployment in the United Kingdom Since the War - Andrews, Martyn; Nickell, Stephen (Review of Economic Studies, 1982)
In this paper, we first present a competitive macroeconomic model of an open economy which is suitable for estimation and contrast this with a non-competitive model. We then derive unemployment equations from the various models and estimate them over annual data from 1948–1979. We draw the following conclusions. (i) The competitive model of the labour market does not fit the facts. (ii) The non-competitive model generates an equation for the constant inflation rate of unemployment which reveals how, at certain times such as the mid 1970s, a combination of factors conspired to raise this level forcing the government into a deflationary stance to prevent inflation rising drastically. (iii) A number of factors have raised the level of unemployment in a secular fashion since the war, in particular the increase in the variation of relative prices, the increase in the benefit to income ratio, the introduction of employment protection legislation and the rise in the intersectoral shifts of the labour force.